Transgelin-2 Involves in the Apoptosis of Colorectal Cancer Cells Induced by Tanshinone-IIA. (27th September 2022) - Zhang, Yingru; Zhao, Yiyang; Liu, Jingwen; Li, Chunpu; Feng, Ying; Jiang, Shasha; Sun, Xiaoting; Hu, Xueqing; Wang, Yan
Abstract : Tanshinone IIA (TanIIA) is the main active ingredient in the fat-soluble components isolated from Salvia miltiorrhiza Bunge. Our previous studies have convincingly proved that TanIIA is an effective drug against human colorectal carcinoma cells. In order to further demonstrate the effect of TanIIA on CRC, we carried out exploratory research about it in vivo and in vitro. The results demonstrated that TanIIA were observably more effective than control group in preventing tumor growth, and it has increased the survival time. Cancer cells viability and proliferation were accompanied by concentration and time dependent decline reached with TanIIA. We found that TanIIA altered the morphology of cytoskeleton and it could obviously induce apoptosis of colorectal cancer cells and block the cells in the G0/G1 phase. TanIIA also increased phosphorylation of p38MAPK, upregulated ATF-2 expression and downregulated Transgelin-2 expression, which could be reversed by SB203580, a p38MAPK-specific inhibitor. Our results suggested that TanIIA could induce apoptosis of colorectal cancer and block the cells in G0/G1 phase involved in downregulating the expression of Transgelin-2 through p38MAPK signal pathway.